PHYSICAL ACTIVITY IN RELATION TO BODY MASS INDEX AND LIFESTYLE IN UNMSM STUDENTS - DAMIÁN-NÚÑEZ, Edgar (2024)
The purpose of the study is to determine the impact of physical activity, body mass index (BMI) and lifestyle on students of the UNMSM Professional School of Physical Education, in the context of the COVID-19 pandemic. The population, 570 students; random sample by saturation 230, as an instrument the questionnaire of lifestyle habits, physical activity and quality of life, for the BMI data sheet, the study was developed in a quantitative approach, type applied causal descriptive design, transactional. To demonstrate the impact, the linear regression coefficient was used, concluding that there is no impact on the quality of life of BMI or physical activity, but there is an impact of healthy living on quality of life, with a predictability of 38.9. %.